What can the 21st century bring for medicine – facts and hopes - Steciwko, Andrzej; Reksa, Dominika (Przewodnik Lekarza/Guide for GPs, 2007)
21st century medicine still faces many problems and new technologies enable us to challenge those tasks which formerly seemed unsolvable. Modern medicine is ever more closely associated with biotechnology and bioengineering, which constitute a strong force in the development of new treatment technologies. Advances in medicine would not be possible without parallel development of other branches of science – molecular biology, informatics, immunology, material engineering and quantum physics. The authors point out some interesting reports in medical sciences including genetics, oncology, diagnostic imaging, surgery and prosthetics, which might become tools in the fight against challenges of everyday general practice and social diseases of the 21st century.